Design of a broadband horn antenna - Ding, Andi (Nanyang Technological University, 2022)
Horn antenna is one typical kind of antenna that has a wide use nowadays. Due to its unique structure and characteristic, it is usually designed to have a broad band and applied to a lot of applications. In this thesis, two specially designed broadband horn antennas are presented.